OPTICAL SCHEME FOR SPECTROPHOTOMETER: OPTICAL SCHEME FOR SPECTROPHOTOMETER - Getzov, Petar; Stoyanov, Stiliyan; Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The work is about the design and development of compact optical system for spectrophotometer. The equation of plain diffraction grating allows the design of a compact appliance with optimal combination of the separate optical elements and their parameters. There are certain constructions of spectral appliances, which are developed by leading companies. The path of the rays is used, it is reflected by mirrors many times and the result is a compact construction. There are company catalogues for the choice of separate optical elements when developing appliances, but they do not describe the elements in detail. These facts do not allow scientific research and experimental construction on a high scientific and technical level with own recourses and materials.